Tissue engineering of vascular/valvular equivalents on the base of the xenogeneic decellularized matrix - Savchuk, M.V. (Вiopolymers and Cell, 2014)
According to the WHO, in 2008 cardiovascular diseases claimed the lives of 17.5 million people (30 % of all diseases). Often the only option to save a patient’s life is a replacing the injured part of an organ by the prosthesis. Aim. This research was aimed to produce biomodificated cardiovascular graft by decellularisation of porcine heart valve. Methods. Our method of decellularization permits to make morphologically and physically non-modified decellularised extracellular matrix. Results. The analysis of matrix shows a decrease of the total number of cells, preservation of the collagen and elastin fibers structure, and safety of physiological adhesion. Conclusions. The matrix can be used as a framework for the vessel-valvular tissue-engineering prosthesis after its recellularization by the recipient’s autologous cells.